2005
DOI: 10.1103/physrevlett.94.070603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phase Noise on Parametric Instabilities

Abstract: We report an experimental study on the effect of an external phase noise on the parametric amplification of surface waves. We observe that both the instability growth rate and the wave amplitude above the instability onset are decreased in the presence of noise. We show that all the results can be understood with a deterministic amplitude equation for the wave in which the effect of noise is just to change the forcing term. All the data for the growth rate (respectively the wave amplitude), obtained for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…2. Its dependence on the reduced control parameter ǫ = (a − a c )/a c is proportional to ǫ 1/4 , as it has been previously reported elsewhere [13]. No distinguishable hysteresis loop is found in the computed bifurcation diagrams.…”
Section: A Parametric Excitationsupporting
confidence: 55%
See 1 more Smart Citation
“…2. Its dependence on the reduced control parameter ǫ = (a − a c )/a c is proportional to ǫ 1/4 , as it has been previously reported elsewhere [13]. No distinguishable hysteresis loop is found in the computed bifurcation diagrams.…”
Section: A Parametric Excitationsupporting
confidence: 55%
“…This leads to an increase of threshold. For instance, this type of mechanism explains the increase of threshold observed for parametric forcing in the presence of phase noise [13]. The modification of the exponent can be also ascribed to an effective detuning if it has the correct sign with respect to the nonlinear frequency correction.…”
Section: Effect Of Spatio-temporal Fluctuations Induced By the Vomentioning
confidence: 99%
“…The curves show a linear dependence on Fr, which indicates the proper choice of a quintic subcritical bifurcation. Moreover, if we consider large values of ϵ in equation (7), and that ν is much smaller than γ for a relatively small bistability region, we obtain ϵ γ ≈ R 4 . From figure 9(b R is close to the mode of R, we can fit both bifurcation curves with the model given by equation (6).…”
Section: Bifurcation Diagramsmentioning
confidence: 87%
“…In general, the existence and stability of the different states in driven systems is affected at different levels by the presence of fluctuations, which can be inherent to the system or added by an external mechanism. Sometimes, the net effect is that of shifting the critical value at which the bifurcation occurs [6,7], whereas in some other cases, the effect of the noise is more drastic and it can even change the nature of the bifurcation (i.e. sub or supercriticality) [8], or the nature of the saturation mechanism [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that chaotic phases decrease the effective amplitude of the external force (Petrelis et al, 2005). Suppose that the wave breaking leads to the Gaussian noise; then, the corresponding decrease in the external forcing may be estimated as (Petrelis et al, 2005) e…”
Section: Discussionmentioning
confidence: 99%